Enhancing the catalytic activity of MnO2 via structural phase transition for propane combustion: Promotional role of ionic liquid. Issue 6 (December 2021) - Sun, Liang; Zhao, Peng; Liu, Yihao; Tan, Bangjie; Yu, Chaoyi; Feng, Nengjie; Wang, Lei; Wan, Hui; Guan, Guofeng
Abstract: A series of manganese dioxide have been synthesized by ionic liquid assisted hydrothermal method and used for propane combustion. 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM-BF4 ] was selected as the structure-directing agent, which could generate extended hydrogen bonds under hydrothermal conditions. These hydrogen bonds could be used for entropy driving of nanostructures self-assembly, thus regulating the growth of crystal. Meanwhile, the existence of [BMIM-BF4 ] could interact with [MnO6 ] octahedron in MnO2 through electrostatic and π-π stacking interactions, eventually leading to the transformation from α-MnO2 to β-MnO2 after calcination. A series of characterization results further indicated that with the assistance of ionic liquid, the morphology of the precursor evolved from nanoflowers to nanorods attached with nanofibers, and the specific surface areas and redox properties were also enhanced. When the molar ratio of KMnO4 to ionic liquid reached 8:1, the obtained Mn-1–500 exhibited the highest catalytic activity for propane combustion. The T90 of propane on Mn-1–500 was about 310 °C, which was nearly 110 °C lower than that of Mn-0–500 prepared without the assistance of ionic liquid. These results could offer a novel strategy for the development of high-performance catalysts. Graphical Abstract: ga1 Highlights: β-MnO2 was synthesized via ionic liquid-assisted hydrothermal method. The introduction of ionic liquid induced the transformation from α-MnO2 to β-MnO2 . Larger specific surface area was generated by the assistance of ionic liquid. The catalyst obtained when the molar ratio of KMnO4 to IL was 8 showed high activity.